2020
DOI: 10.1111/jog.14543
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness measured by cardio‐ankle vascular index is greater in non‐obese young women with polycystic ovarian syndrome

Abstract: Aim The association of metabolic abnormalities and polycystic ovarian syndrome (PCOS) has been documented, but few studies have focused on cardiovascular risk in these women. The aim of this study was to compare arterial stiffness by using the cardio‐ankle vascular index (CAVI) in PCOS women with controls, and to evaluate whether any clinical or laboratory variables had independent associations with it. Methods A group of 160 women, matched for age and body mass index were recruited. Diagnosis of PCOS was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Due to the unfavorable cardio-metabolic profile, women with PCOS are considered at increased risk for cardiovascular disease (CVD). In fact, previous studies exploring subclinical atherosclerosis showed increased carotid-intima media thickness and arterial stiffness, and impaired flow mediated dilatation [4,17,18]. Moreover, several large cohort studies confirmed that these women are at increased risk for CVD [19,20].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to the unfavorable cardio-metabolic profile, women with PCOS are considered at increased risk for cardiovascular disease (CVD). In fact, previous studies exploring subclinical atherosclerosis showed increased carotid-intima media thickness and arterial stiffness, and impaired flow mediated dilatation [4,17,18]. Moreover, several large cohort studies confirmed that these women are at increased risk for CVD [19,20].…”
Section: Discussionmentioning
confidence: 91%
“…PCOS is diagnosed when oligo-anovulation, polycystic ovarian morphology (PCOM), biochemical and/or biochemical hyperandrogenism (HA) and their combinations are present, which forms the phenotypes [3]. Besides its reproductive complications such as oligo-anovulation and infertility, PCOS also carries a considerable risk of future medical comorbidities and long-term risks including insulin resistance, diabetes mellitus, hypercholesterolemia, cardiovascular disorders, and microvascular dysfunction [4][5][6]. To date, the exact pathophysiology of the development of PCOS and PCOS phenotypes is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Armeni et al reported that AS, evaluated by pulse wave velocity and augmentation index, was increased in asymptomatic nondiabetic postmenopausal women(mean age 55.6±7.8 years) with PCOS (7). Similarly, AS measured by cardio-ankle vascular index was found to be greater in young nonobese women with PCOS (mean age 22.90±3.04 years) compared to subjects without PCOS (6). Besides age, BP has been verified as another common factor that influences AS (27).…”
Section: Discussionmentioning
confidence: 98%
“…However, the impact of PCOS on future CVD risk should not be overlooked, and opportunities to implement CVD prevention strategies in these women should be prioritized ( 3 ). Arterial stiffness(AS) is known to play a predictive role in CVD ( 4 ), and clinical data show that AS is increased in women with PCOS ( 5 , 6 , 7 ). Automated computer-assisted brachial-ankle pulse wave velocity (baPWV) is a diagnostic method to investigate AS that has been recommended in large-scale sample studies ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…An important cohort for investigating this is patients with polycystic ovary syndrome (PCOS), a condition commonly characterised by hyperandrogenism, irregular/missing menstruation, and ovarian cysts. Excess testosterone increases systemic arterial stiffness in PCOS patients compared to controls (Kilic et al, 2021) but the influence on cerebrovascular function is vastly under-researched. Acar et al (2005) reported no statistically significant difference in CBV using colour duplex sonography, though blood velocity in the vertebral artery was significantly reduced in PCOS patients.…”
Section: Testosteronementioning
confidence: 99%